2012
DOI: 10.1101/gr.140236.112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide genetic variations are highly correlated with proximal DNA methylation patterns

Abstract: 5-methyl-cytosines at CpG sites frequently mutate into thymines, accounting for a large proportion of spontaneous point mutations. The repair system would leave substantial numbers of errors in neighboring regions if the synthesis of erased gaps around deaminated 5-methyl-cytosines is error-prone. Indeed, we identified an unexpected genome-wide role of the CpG methylation state as a major determinant of proximal natural genetic variation. Specifically, 507 Mbp (~18%) of the human genome was within 10 bp of a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 42 publications
2
61
2
Order By: Relevance
“…5 Briefly, 'N-back' refers to how far back in the sequence of stimuli the subject had to recall. The stimuli consisted of numbers (1)(2)(3)(4) shown in random sequence and displayed at the points of a diamond-shaped box. There was a visually paced motor task, which also served as a non-memory guided control condition (0-back) that simply required subjects to identify the stimulus currently seen.…”
Section: Working Memory (Wm) Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Briefly, 'N-back' refers to how far back in the sequence of stimuli the subject had to recall. The stimuli consisted of numbers (1)(2)(3)(4) shown in random sequence and displayed at the points of a diamond-shaped box. There was a visually paced motor task, which also served as a non-memory guided control condition (0-back) that simply required subjects to identify the stimulus currently seen.…”
Section: Working Memory (Wm) Taskmentioning
confidence: 99%
“…1 CpG methylation state is recognized as a major determinant of natural genetic variation, 2 and a strong genetic component underlies inter-individual variation in DNA-methylation profiles. 3 While it has been argued that many SNPs contribute to geneexpression changes and phenotypes relevant for diseases via epigenetic mechanisms, 3,4 the possibility that DNA methylation changes may compensate and/or modulate the effect of genetic variation has been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the global genomic distribution of epigenetic modifications in medaka blastula embryos, we performed ChIP-seq analyses using antibodies against H3K27me3, H3K4me1, H3K4me2, H3K4me3 and H3K27ac (supplementary material Table S1), and integrated these results with previously established medaka single-base DNA methylomes (Qu et al, 2012). At the blastula stage, methylation frequency of individual CpG sites has a clear bimodal distribution (supplementary material Fig.…”
Section: Identification Of Hypomethylated Domains In the Medaka Genomementioning
confidence: 99%
“…To address whether HMD shortening at active gene loci is a general feature in adult tissues, we compared the epigenomes of the adult dorsal myotome and liver with that of blastula embryos. For liver epigenome data, we generated histone modification maps (supplementary material Table S1), and integrated these with methylome data from a previous study (Qu et al, 2012). We found that the majority of K27HMDs have unchanged methylation levels in adult tissues, but a significant proportion of HMDs were subjected to DNA hypermethylation in which more than 5% of their CpG sites became highly methylated (>0.4) ( Fig.…”
Section: Hmd Shortening Associates With Sustained Gene Expression In mentioning
confidence: 99%
See 1 more Smart Citation